ANALISIS BERLARUT-LARUTNYA PROSES PENANDATANGANAN KEMBALI MoU ANTARA INDONESIA-CINA DALAM MENANGGULANGI MASALAH NARKOBA PERIODE 2008-2015 - Saputra, Dea Tunjung Jatra; Windiani, Reni; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Drug becomes important issues because they are threatening allaround countries. A transnational drugs trafficking as in the fase ofIndonesia-China conducted by an international syndicate resulted in aloss of both sides. On December 2, 2003 Indonesia and China agreedto sign a Memorandum of Understanding to combat transnationalcrime, cooperate of narcotics and drugs. Cooperation is carried outby The Indonesia National Police and The Ministry of Public Securityof China. Cooperation agreed upon by the two countries was valid forfive years, before needing a renewal on December 2, 2008. Theresigning process has been slow where several factors have indicatedthat two governments might have not been fruitful. Based on datamining through interviews, the result of this research is process resignatories,because there are several factors such as the existence ofthe counter draft, distribution of authority through the Mutual LegalAssistence system and the differences in the system of government.